Microbial contamination in Brazilian beef - Sousa, Izabela Marques; Chaves, Karina da Silva; Ribeiro-Brasil, Danielle Regina Gomes (Revista de Ciências Agroveterinárias, 2025)
Ensuring the quality of food products such as beef is extremely important to prevent outbreaks of food contamination caused by the presence of pathogenic bacteria, guaranteeing the physiological well-being of human beings, reducing the number of cases of contamination, and thus avoiding it becoming a public health problem. This study aimed to gather information from articles on microbial contamination in beef in Brazil using the scientometric method. Articles were searched using the academic platforms Scopus, Pubmed, and Scielo for keywords (“Escherichia coli” OR “Staphylococcus aureus” OR Listeria OR Salmonella OR “Lactobacillus Fermentum” OR Enterobacteria OR mesophiles OR Stecs) AND beef OR “carne bovina”. The survey selected 69 articles that met the inclusion criteria for the study. The South, Southeast, and Center-West regions had the most studies evaluating the microbiological quality of beef. For the Southeast, this may be associated with the greater number of people living in the region and higher education institutions, while for the Midwest, it may be due to the potential for commercialization. Correlating the predominance of these two regions, they also had the highest number of articles analyzed, specifically São Paulo and Mato Grosso. We conclude that for beef quality to be guaranteed, preventive measures must be taken to monitor and improve sanitary conditions, from slaughter to marketing, so that products become increasingly reliable and do not pose a risk to public health.